Effect of Lasalocid on the sexual development of beef heifers - Corah, L.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Lasalocid (Bovatec®) improved daily gain of replacement heifers by .20 lb per day and reduced the time to first heat in heifers fed on a lower level of energy, but had no significant affect in the higher energy group. Feeding Lasalocid did not affect conception rates.
Keywords: Beef; Lasalocid; Gain; Conception rate